L’écriture du terroir revisitée : La Rage de Louis Hamelin - Resch, Yannick (Romanica Silesiana)
The article focuses on ironic references to the traditions of rural literature in Jean Hamelin’s The Rage. The author explores the concept of the “writing of excess,” and claims that whereas actual country is an evanescent category, the territory that one can possess is that of language. Key-words: Intertextuality, rural novel (roman de la terre), irony , writing of excess.